Arabidopsis CLAVATA1 and CLAVATA2 receptors contribute to Ralstonia solanacearum pathogenicity through a miR169‐dependent pathway. Issue 2 (14th March 2016) - Hanemian, Mathieu; Barlet, Xavier; Sorin, Céline; Yadeta, Koste A.; Keller, Harald; Favery, Bruno; Simon, Rüdiger; Thomma, Bart P. H. J.; Hartmann, Caroline; Crespi, Martin; Marco, Yves; Tremousaygue, Dominique; et al.
Summary: Bacterial wilt caused by Ralstonia solanacearum is one of the most destructive bacterial plant diseases. Although many molecular determinants involved in R. solanacearum adaptation to hosts and pathogenesis have been described, host components required for disease establishment remain poorly characterized. Phenotypical analysis of Arabidopsis mutants for leucine‐rich repeat (LRR)‐receptor‐like proteins revealed that mutations in the CLAVATA1 ( CLV1 ) and CLAVATA2 ( CLV2 ) genes confer enhanced disease resistance to bacterial wilt. We further investigated the underlying mechanisms using genetic, transcriptomic and molecular approaches. The enhanced resistance of both clv1 and clv2 mutants to the bacteria did not require the well characterized CLV signalling modules involved in shoot meristem homeostasis, and was conditioned by neither salicylic acid nor ethylene defence‐related hormones. Gene expression microarray analysis performed on clv1 and clv2 revealed deregulation of genes encoding nuclear transcription factor Y subunit alpha (NF‐YA) transcription factors whose post‐transcriptional regulation is known to involve microRNAs from the miR169 family. Both clv mutants showed a defect in miR169 accumulation. Conversely, overexpression of miR169 abrogated the resistance phenotype of clv mutants. We propose that CLV1 and CLV2, two receptors involved in CLV3 perception during plant development, contribute to bacterial wilt through a signalling pathway involving the miR169/NF‐YA module.